TOB1 Blocks Intestinal Mucosal Inflammation Through Inducing ID2-Mediated Suppression of Th1/Th17 Cell Immune Responses in IBD - Lin, Ritian; Ma, Caiyun; Fang, Leilei; Xu, Chunjin; Zhang, Cui; Wu, Xiaohan; Wu, Wei; Zhu, Ruixin; Cong, Yingzi; Liu, Zhanju (Cellular and molecular gastroenterology and hepatology, 2022)
TOB1 is an anti-proliferative protein of Tob/BTG family and typically involved in the tumorigenesis and T cell activation. Although TOB1 is associated with T helper 17 cell–related autoimmunity, its role in modulating T cell–mediated immune responses in IBD remains poorly understood. Here, we explored its expression and the underlying mechanisms involved in the pathogenesis of inflammatory bowel disease (IBD). TOB1 and ID2 expression in IBD patients was examined by quantitative real time polymerase chain reaction and immunohistochemistry. IBD CD4+ T cells were transfected with lentivirus expressing TOB1, ID2, TOB1 short hairpin RNA and ID2 short hairpin RNA, respectively, and Tob1–/–CD4+ T cells were transfected with lentivirus expressing Id2. Experimental colitis was established in Tob1–/– mice by trinitrobenzene sulfonic acid enema and in Rag1–/– mice reconstituted with Tob1–/–CD45RBhighCD4+ T cells to further explore the role of Tob1 in intestinal mucosal inflammation. Splenic CD4+ T cells of Tob1–/– mice were sorted to determine transcriptome differences by RNA sequencing. TOB1 expression was decreased in inflamed mucosa and peripheral blood CD4+ T cells of IBD patients compared with healthy subjects. Overexpression of TOB1 downregulated IBD CD4+ T cells to differentiate into Th1/Th17 cells compared with control subjects. Severe colitis was observed in Tob1–/– mice through trinitrobenzene sulfonic acid enema or in Rag1–/– mice reconstituted with Tob1–/–CD45RBhighCD4+ T cells, compared with control animals. RNA sequencing analysis revealed ID2 as functional target of TOB1 to inhibit IBD CD4+ T cell differentiation into Th1/Th17 cells. Mechanistically, TOB1 was associated with Smad4/5 to induce ID2 expression and restrain Th1/Th17 cell differentiation. TOB1 restrains intestinal mucosal inflammation through suppressing Th1/Th17 cell–mediated immune responses via the Smad4/5-ID2 pathway. It may serve as a novel therapeutic target for treatment of human IBD. [Display omitted]